2019
DOI: 10.26825/bup.ar.2019.007
|View full text |Cite
|
Sign up to set email alerts
|

Review on the titanium oxide for catalytic applications

Abstract: Titanium dioxide (TiO2) presents particular importance, due to its general properties in a wide range of fields, such as catalysis, photocatalysis and antibacterial agents and as nano-paint (self-cleaning). Physical and chemical characteristics of TiO2, particle size and shape, phases of crystalline TiO2 with band gaps that rutile TiO2 of 3.0 eV and anatase TiO2 of 3.2 eV, determine the photocatalytic performance of TiO2. This review presents the theoretical concepts of the structure properties of this oxide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For anatase, the ultra-band gap illumination is limited to near UV light (λ < 385 nm), whereas rutile has a tail that extends the response into visible light (λ < 410 nm) [9]. While it is widely reported that anatase has lower rates of recombination and hence, higher photo-reactivity than rutile, these differences may be diminished under certain conditions and both materials may generate radical products that promote degradation of the oil binder [10][11][12][13][14]. Furthermore, the behavior of semiconductor pigments such as TiO 2 is influenced by interactions with other components present in the complex matrix of a paint film, such as inorganic and organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For anatase, the ultra-band gap illumination is limited to near UV light (λ < 385 nm), whereas rutile has a tail that extends the response into visible light (λ < 410 nm) [9]. While it is widely reported that anatase has lower rates of recombination and hence, higher photo-reactivity than rutile, these differences may be diminished under certain conditions and both materials may generate radical products that promote degradation of the oil binder [10][11][12][13][14]. Furthermore, the behavior of semiconductor pigments such as TiO 2 is influenced by interactions with other components present in the complex matrix of a paint film, such as inorganic and organic compounds.…”
Section: Introductionmentioning
confidence: 99%